Culture of Marine Sciaenids in Low Salinity: an Opportunity for Expanded Aquaculture in Mexico - González-Félixa, Mayra L.; Perez-Velazquez, Martin; Ibarra-Garciaparra, Germán E.; Trujillo-Villalba, Jorge (Facultad de Ciencias Biologicas, 2017)
The Sciaenidae is a highly diversified family of fish with worldwide distribution across warm-temperate andtropical waters. Numerous sciaenids are cultured commercially in different regions of the world. Mostsciaenids are marine, but many representatives are euryhaline, i.e., capable of withstanding a wide range ofenvironmental salinities. Surprisingly enough, the family encompasses 25 strict freshwater species within sixgenera. Evidence of the salinity tolerance of various species of sciaenids across the world is large enough tosuggest that commercial culture of sciaenids in low salinity is possible. In Mexico, among finfish familiessubjected to fisheries in the Pacific Ocean, Sciaenidae contributes with the largest number of captured species(24 species), while 13 species of sciaenids are captured in the Gulf of Mexico and the Caribbean Sea. Besidesthe 37 species exploited in commercial fisheries, there are more representatives of this family in Mexico. Forexample, at least 30 species of sciaenids are found in the Gulf of California alone. Taking into account thisrichness of species, some have been evaluated as candidates for aquaculture, including totoaba (Totoabamacdonaldi), the Gulf corvina (Cynoscion othonopterus), and the shortfin corvina (C. parvipinnis). All threespecies have shown to be euryhaline. For T. macdonaldi, definite proof that it can be cultured to marketablesize in low salinity is presented. The information herein presented provides opportunities for expandedaquaculture of sciaenids in Mexico, using a variety of water sources, such as brackish or diluted saltwater,rivers, dams, or ground waters, perhaps in locations in which commercial culture was not previously thoughtpossible.